Comparison of Health-Related Quality of Life in Different Types of Chronic Ankle Instability - Hadadi, Mohammad; Heghighat, Farzaneh; Hossein, Iman (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Introduction People with chronic ankle instability (CAI) have decreased health-related quality of life (HRQOL), but the differences in HRQOL status between subgroups of CAI have not been determined. This observational, cross-sectional study aimed to evaluate and compare physical, social and psychological aspects of HRQOL in subgroups of patients with CAI.Methods Ninety patients with CAI and 30 healthy participants were included. The patients were assigned to 3 subgroups with functional ankle instability (FAI), mechanical ankle instability (MAI), or mixed functional and mechanical instability (MIX), based on the talar tilt test, anterior drawer test, and Cumberland Ankle Instability Tool score. Participants completed the self-assessed Foot and Ankle Ability Measure (FAAM), Tampa Scale of Kinesophobia-11 (TSK-11), Fear-Avoidance Beliefs Questionnaire (FABQ), and Short-Form Health Survey (SF‑36).Results Significant differences were observed between healthy participants and each CAI subgroup in regional (FAAM), psychological (TSK-11 and FABQ) and global (SF-36) measures (p<0,05). The MIX subgroup had a significantly lower score on the FAAM-sport component, and a higher score on the TSK-11 and FABQ (p<0,05), than the FAI subgroup. There were no diffirences between other CAI subgroups in quality of life measures.Conclusions Patients with MAI and FAI had similar functional deficits in activities of daily living and sport activities, and greater fear of re-injury. The MIX subgroup had greater deficits in sport activities and greater fear of re-injury than the FAI subgroup.
Keywords: Chronic ankle instability; Mechanical ankle instability; Functional ankle instability; Health-related quality of life